Pharmaceutical standardization and physicochemical characterization of traditional ayurvedic mineral drug red ochre roasted in cow's ghee (Shuddha Gairik) - Chavan, S. B.; Gupta, V. S.; Deshmukh, V. V.; Sardeshmukh, S. P. (Indian Journal of Traditional Knowledge, 2022)
Rasashastra is a pharmaceutics branch of Ayurveda describing scientific methods to convert metals and minerals into bio-compatible formulations used individually or plant admixed to enhance their bioavailability and efficacy. In the present study, red ochre (Gairik) powder was processed in cow's ghee by textual method of roasting. The steps of preparation and changes in the properties therein were documented and validated in triplicate batches to develop a monograph. Ayurvedic and basic tests were performed to determine the properties of Shuddha Gairik. The physical characterization included Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infra-red (FT-IR), Dynamic Light Scattering (DLS) and Thermo-gravimetric Analysis (TGA). Elemental composition was estimated by titration and gravimetric analysis while heavy metal limits were assessed using Inductively Coupled Plasma Optical Emission Spectrophotometry (ICPOES). This study depicted that crude red ochre, containing Kaolinite with high iron percentage, on roasting in cow's ghee led to the formation of fatty acids adsorbed red ochre particles. The developed monograph will be a guideline to the Ayurvedic industry for precise formulation of Shuddha Gairik. This will help researchers for better understanding the importance of Ayurvedic methods of pharmaceutical preparations and carry out their mechanistic studies in various diseases.
Keywords: Ferric oxide; Gairik; Kaolinite; Monograph; Red ochre; Roasting